Is the Collective Model of Labor Supply Useful for Tax Policy Analysis? A Simulation Exercise - Olivier Bargain; Nicolas Moreau (Center for Economic Studies and ifo Institute (CESifo), 2003)
The literature on household behavior contains hardly any empirical research on the withinhousehold distributional effect of tax-benefit policies. We simulate this effect in the framework of a collective model of labor supply when shifting from a joint to an individual taxation system in France. We show that the net-of-tax relative earning potential of the wife is a significant determinant of intrahousehold negotiation but with very low elasticity. Consequently, the labor supply responses to the reform are entirely driven by the traditional substitution and income effects as in a unitary model. For some households only, the reform alters the intrahousehold distribution in a way that tends to change normative conclusions. A sensitivity analysis shows that the collective model would be required if the tax reform was both radical and of extended scope.
Keywords: 330; collective model; intrahousehold allocation; household labor supply; tax reform